MIND MAPPING TOOL FOR NOTE TAKING - Fariz Izwan, Ishak (Universiti Malaysia Sarawak (UNIMAS), 2015)
Mind mapping is a brainstorming technique that has various applications. Mind mapping technique usually used in note taking, studying and critical thinking. It also focus on key points and short will make students understand topics easily. We introduced a mind mapping tool (MMT) to help student in note taking. The mind mapping tool is a stand-alone computer program which will make use of existing open source technology. The technologies include Java and XML. MMT will help student to make effectively: shorter time to complete the note, more compact and organized notes. MMT will help to ensure student to understand the key point in certain subjects. Rational Unified Process (RUP) methodology has been used, for completing this project. MMT will serve as medium for students to take notes in lecture and can replace paper notes.